Idiopathic gastroparesis in a female collegiate swimmer - Nestrowitz, S.; Gildard, M.; Powers, M. E. (Journal of Athletic Training, 2019)
Background: A 19 year old female Division I swimmer reported to her athletic trainer complaining of gastrointestinal discomfort. Her personal and family history were negative for diabetes however there was a family history of Crohn's Disease. Her chief complaints were nausea, vomiting, epigastric pain, diminished appetite, and loose bowel movements. The patient reported similar issues had occurred several weeks earlier and were relieved by discontinuing dairy intake. However, at this time, the symptoms did not appear to be associated with a specific dietary intake. By the time the patient reported her symptoms she had very limited caloric and foodvariety intake but had no significant weight loss. Differential Diagnosis: Crohn's Disease, Gastric ulcer, Gastroenteritis, Gastroparesis, Giardiasis, Infl ammatory bowel disease, Lactose intolerance. Treatment: Upon referral to a gastroenterologist, the patient underwent stool and blood samples which were negative for helicobacter pylori, gastric cancer, and pepticulcer disease. A colonoscopy was performed and was unremarkable. Later, the patient complained of blood in her stool which was determined to be caused by hemorrhoids. Based on her clinical presentation and unremarkable diagnostic testing, the patient was diagnosed with idiopathic gas-troparesis. Omeprazole and Zofran were prescribed to alleviate her nausea and vomiting. While gastroparesis may be confirmed via scintigraphy or gastric endoscopy, her physician felt these were unnecessary. A diet high in starches, low in fruits and vegetables, and excluding alcohol was recommended which the patient followed briefly but discontinued due to no relief in her symptoms. Maintenance of proper hydration and electrolyte levels were also strongly recommended and this did seem to aid the patient's symptoms. Several months after the diagnosis, the patient revealed to her athletic trainer that she had also been suffering from bulimia nervosa for several years. She was subsequently referred to counseling services. The presence of an eating disorder posed complications in the physical manifestation and management of her gastroparesis especially considering the potential for stress and anxiety to develop in a patient due to the symptoms of gastroparesis. The patient was able to continue sport participation at a high level despite her condition. She continues treatment for her gastroparesis and disordered eating while swimming competitively. Uniqueness: Gastroparesis is a chronic disorder that causes delayed gastric emptying in the ab-sence of mechanical obstruction and often presents with gastric pain. While some cases of gastroparesis are classifi ed as id-iopathic, the condition is more commonly seen in patients with diabetes mellitus. In addition, gastroparesis is most commonly diagnosed in females approximately 40 years of age. The prevalence of gastropa-resis is about 0.2% but there is an overall lack of epidemiological studies. Our pa-tient was outside the normal age range for diagnosis and did not suffer from diabetes mellitus, a common comorbidity to gas-troparesis. Her bulimia nervosa added to the complexity of this case. Conclusions:Gastroparesis can be a diffi cult condi-tion to diagnose and manage particularly for the interscholastic or college athletic trainer. It is an uncommon condition and may be idiopathic. It has been theorized that a potential change in electrical signal between the stomach's interstitial cells of Cajal could trigger gastroparesis. Gastric pain is the most common symptom but is often overlooked and underreported by patients. The association of gastropa-resis with diabetes mellitus, idiopathic nature, and proclivity to lead to psycho-social issues in patients requiring a mul-tidisciplinary approach to treatment. It has also been reported that the addition of psychological treatment may benefi t pa-tients diagnosed with gastroparesis due to the stress and anxiety associated with the condition.